2019
DOI: 10.29057/icbi.v7i13.3447
|View full text |Cite
|
Sign up to set email alerts
|

Un ejemplo de mala praxis ambiental: Tekchem en Salamanca, Gto.

Abstract: México figura dentro de los primeros quince países en donde han ocurrido los más grandes accidentes industriales entre 1917 y 2011. El accidente ocurrido en Tekchem, una planta de agroquímicos ubicada en Salamanca, Guanajuato es uno de los doce eventos acaecidos en nuestro país en el periodo mencionado. En este estudio se hace una revisión de cómo este accidente forzó a las autoridades ambientales a prestar atención a un pasivo ambiental que se formó durante casi 50 años, mismo que hasta la fecha continua sin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The environmental liabilities generated were the result of an accumulation of several years due to inconveniences in terms of waste disposal. Previous studies have characterized the polluting substances in the site, mainly reporting the presence of OCPs, which constitute 70% of the polluting mass (Beltrán Hernández et al 2019;SEMARNAT 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental liabilities generated were the result of an accumulation of several years due to inconveniences in terms of waste disposal. Previous studies have characterized the polluting substances in the site, mainly reporting the presence of OCPs, which constitute 70% of the polluting mass (Beltrán Hernández et al 2019;SEMARNAT 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is a particular case related to contamination by OCPs in the place: the facilities and surroundings of the former Tekchem Industrial Unit, in which organochlorine and organophosphate pesticides were manufactured, among other dangerous compounds. The company operated between 1943 and 2007, however, to date there is a problem of soil and groundwater contamination due to the inadequate management of processes and waste during most of the production stages (Albert and Jacott 2015;Beltrán Hernández et al 2019). An environmental risk assessment study at the site showed that the soil is mostly contaminated by OCPs, representing approximately 70% of the identi ed compounds, with DDT and its metabolites being found in the highest concentrations (SEMARNAT 2018).…”
Section: Introductionmentioning
confidence: 99%